Examination of changes in body composition depending on the training process in athelets - Marković, Marija; Đelić, Marina (Medicinski podmladak, 2026)
Introduction: It is well known that continuous physical activity causes adaptive changes in all organ systems, and they are most noticeable in the body composition parameters. Therefore, it is important to monitor the body composition parameters of top athletes, considering that their overall result depends on them.Aim: Examination of dynamics of changes in body composition depending on the period of the training process in athletes.Material and Methods: The research included 152 top athletes - male soccer players (18 to 40 years old), who at the time of the investigation were actively involved in competitive sports and trained at least 3 times and more than 10 hours a week. All data were analyzed from available medical records over a period of 16 years.Results: There is no significant statistical difference at the beginning and end of the season for all variables except for the amount of fat in kilograms and the percentage of fat.Conclusion: According to the results in the examined group of top athletes, the change in body composition does not depend on the training process. The only notable changes were observed in the amount of fat and body fat percentage.Keywords: body composition; athletes; BMI; BF
Keywords: body composition; athletes; BMI; BF